Applicability of various mixing rules for hot asphalt recycled binders. Issue 11 (2nd November 2022) - Sharma, Ankit; Ransinchung R.N., G.D.; Kumar, Praveen
Abstract : In the mix design process of recycled asphalt pavement, the proportion of reclaimed asphalt pavement (RAP) binder and recycling agent (RA) are decided using mixing rules. However, the efficacy of mixing rules remains a concern due to the assumption of 100% blending between RAP binder and RA. This study revisits the applicability of different mixing rules viz. pure mixing rules, mixing rule with binary interaction parameter, and mixing rule with viscosity blending index (VBI). In this study, nineteen RAP-RA pairs were blended at multiple levels of RAP content. The difference between measured and modeled values was analysed using the chi-square test. The statistical analysis of the limited data set proved that the high performance grade (PG) temperature, softening point, Grunberg & Nissan, and phase angle mixing rules are satisfactory in predicting the property of recycled binders.